ANALISIS KINERJA LAPORAN KEUANGAN BADAN AMIL ZAKAT NASIONAL (BAZNAS) GRESIK PERIODE 2021-2024 - Mahdi, Muhammad; Ahmad Farial Wahib H; Ani Qotuz Zuhro' Fitriana (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study analyzes the financial performance of the National Amil Zakat Agency (BAZNAS) in Gresik Regency during the 2021–2024 period using financial ratio analysis. The objectives are to evaluate the efficiency and effectiveness of managing zakat, infaq, and alms (ZIS) funds, identify financial growth trends, and examine internal and external factors influencing the institution's performance. A descriptive quantitative method was applied using secondary data from annual financial reports. The results indicate that BAZNAS Gresik's financial performance varied annually, influenced by post-pandemic economic conditions, beneficiary needs, and internal management strategies. In 2021 and 2024, fundraising efficiency was relatively low, while program expenses remained high. However, the institution successfully maintained operational stability and enhanced transparency through technology utilization. It is concluded that BAZNAS Gresik performed reasonably well, with room for improvement in working capital management and fundraising optimization.